The Palmer ice core as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - Thomas, Elizabeth R; Vladimirova, Diana O; Tetzner, Dieter R; Emanuelsson, Daniel B; Humby, Jack; Turner, Simon D; Rose, Neil L; Roberts, Sarah L; Gaca, Pawel; Cundy, Andrew B
The remote Antarctic continent, distant from human industrial activity, should be one of the last places on Earth to capture Anthropogenic change. Hence, stratigraphic evidence of pollution and nuclear activity in the Antarctic provides proof of the global nature of the Anthropocene epoch. We propose an Antarctic Peninsula ice core candidate for the Global boundary Stratotype Section and Point (GSSP) to the onset of the Anthropocene. The Palmer ice core captures the first evidence of spheroidal carbonaceous fly ash particles (SCPs), resulting from high temperature combustion deposited in Antarctic ice. SCPs first appear in 1936 CE, preceding the rise in plutonium ( 239+240 Pu) concentrations from 1945 CE onwards. GSSP 1952 CE occurs at a depth of 34.9 m, coincident with the peak in 239+240Pu the primary marker for this site.